2019
DOI: 10.1016/j.colsurfa.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and emulsifying properties of the electrostatic complex of β-lactoglobulin fibril and gum Arabic (Acacia Seyal)

Abstract: ℃, 30 min) and salting (200 mM NaCl) environments, and the emulsions were stable during long-term storage (46 days).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…ζ‐Potential values are indicative of the contribution of electrostatic forces towards emulsion stability. Usually, strong electrostatic interactions occur between positively charged proteins and negatively charged polysaccharides, which improve the surface activity of biopolymers (Gao et al , ). The ζ‐potential values showed that the interfacial charge of all emulsions was negative (Table ) and remained relatively constant after fifteen days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…ζ‐Potential values are indicative of the contribution of electrostatic forces towards emulsion stability. Usually, strong electrostatic interactions occur between positively charged proteins and negatively charged polysaccharides, which improve the surface activity of biopolymers (Gao et al , ). The ζ‐potential values showed that the interfacial charge of all emulsions was negative (Table ) and remained relatively constant after fifteen days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Protein–polysaccharide complexes can be formed via electrostatic or hydrogen bonding interactions, which may impact emulsion formation or stability. The kinetics of adsorption is a crucial factor affecting emulsion formation, with smaller droplets being formed for emulsifiers that adsorb faster (Gao et al., 2019). The kinetics of emulsifier adsorption (under quiescent conditions) can be conveniently determined by measuring the change in interfacial tension or interfacial pressure over time (McClements, 2015; Zhao et al., 2015).…”
Section: Mixed Layer Interfaces Prepared By Direct Mixing Methodsmentioning
confidence: 99%
“…Gao et al. (2019) proposed mechanisms for the adsorption of β‐lactoglobulin fibrils and gum arabic at oil–water interfaces (Figure 3). The surface activity and adsorption of pure gum arabic are relatively poor, which results in the formation of a loose interfacial layer.…”
Section: Mixed Layer Interfaces Prepared By Direct Mixing Methodsmentioning
confidence: 99%
See 2 more Smart Citations